The Influence Of Promotion Strategy Through Online Marketing And Word Of Mouth Marketing On The Purchasing Decision Of Zeneos Brand Tire Products PT Gajah Tunggal Tbk. (Case Study at 8 semester Pamulang University Students, Majoring in Management Program for Academic Year 2018/2019) - Eko Juniharto; Ali Mubarok; Arief Budi Santoso (Jurnal Pemasaran Kompetitif, 2020)
Abstract. The purpose of this research is to find out and provide empirical evidence of the influenceof promotional strategies through online marketing and word of mouth marketing partially andsimultaneously on the decision to purchase Zeneos brand motorcycle tire products from PT GajahTunggal Tbk. at Pamulang University in 8 Semester Students, majoring in Management StudyProgram Faculty of Economics, Academic Year 2018/2019. The sampling method uses simple randomsampling technique with the type of research used is associative quantitative. The sample used was100 respondents namely Pamulang University Students 8 Semester, majoring in Management StudyProgram Faculty of Economics, Academic Year 2018/2019. While the data collection method uses thequestionnaire (questionnaire) method. Data analysis methods are validity test, reliability test, classicassumption test, multiple linear regression, correlation, coefficient of determination, and hypothesistesting (partial and simultaneous).The results of this study indicate that there is a positive andsignificant effect both partially and simultaneously between promotional strategies through onlinemarketing and word of mouth marketing on purchasing decisions for Zeneos motorcycle tire productsfrom PT Gajah Tunggal Tbk. at Pamulang University Students Semester 8, S1 Management StudyProgram Faculty of Economics, Academic Year 2018/2019, this is indicated by the results of the t testand f test with a significance value below 0.05.Keywords: Online Marketing; Word of Mouth Marketing; Purchasing Decisions.